Investigation of Novel Hybrid Europium/TEMPTMA-based Neutral pH Aqueous Redox Flow Batteries - Tuna, Ali; Peljo, Pekka (Turkish Chemical Society, 2025)
In this study, Eu3+/TEMPTMA-based hybrid aqueous redox flow battery system at 1.35 V in neutral pH containing 1 M KCl media was introduced and this battery system was monitored for a long-term cycling performance. During battery and electrochemical studies, capacity change, self-discharge rate and coulombic efficiencies are examined and diffusion constant (D0) values are calculated for Eu3+ and TEMPTMA respectively. As a result, the adopted Eu3+/TEMPTMA-based aqueous redox flow battery system exhibits good performance, reversibility and stability such as >99.97% per cycle (>99.88% per day) discharge capacity within containing 0.25 M Eu3+ in 1 M KCl as negolyte at 120 cycles and 29 days battery testing against little excess of 0.5 M TEMPTMA in 1 M KCl as posolyte.